The Effect of the Audit Quality on the Extend of Voluntary Shari'a Disclosure - Ilham, Ratih Milati; Yarisma, Fithri Widyanita (Journal of Economics and Public Health, 2023)
The purpose of the study was to obtain empirical evidence regarding the effect of the Audit Quality on the Extend of Voluntary Shari'a Disclosure. This research is a field research using a quantitative descriptive approach using a purposive sampling method from companies listed on the Indonesia Stock Exchange in 2018. There are 22 companies that meet the criteria as research samples. The results showed that the Audit Quality had no effect on the Extend of Voluntary Shari'a Disclosure.